2012
DOI: 10.4103/1319-2442.100869
|View full text |Cite
|
Sign up to set email alerts
|

Depression in patients on hemodialysis and their caregivers

Abstract: Depression is recognized as the most common psychiatric problem in patients with end-stage renal disease. Stress negatively affects the quality of life of not only the patients on hemodialysis but also their caregivers. The objective of this study was to measure and compare the frequency of depression in these patients and their attendants, and to assess the associated risk factors in both groups. A cross-sectional study was conducted at our hemodialysis unit from June to September 2009. A total of 180 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…Therefore, our results are similar to findings from other studies which identified worse physical performance but better mental health in older people [ 22 ]. A suggestion for these two groups would be to raise their awareness about the disease, making it more tolerable both physically and emotionally for patients and their families [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our results are similar to findings from other studies which identified worse physical performance but better mental health in older people [ 22 ]. A suggestion for these two groups would be to raise their awareness about the disease, making it more tolerable both physically and emotionally for patients and their families [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Men obtained significantly higher scores in all scales (except physical role), including PS (Physical Summary) and MS (Mental Health Summary), while women had the worst QOL [ 19 ]. These findings may be explained by the fact that women are more prone to suffering from depression [ 15 , 16 ], they experience greater pain in chronic diseases [ 20 ], and take on greater responsibility to adapt their lives to their new CKD reality [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although establishing the diagnosis of depression by a psychiatrist is more reliable than questionnaire assessment, our patients favored the survey approach. One obvious strength of the study protocol was to minimize the effects of overlapping symptoms of uremia as much as possible and to correlate the adequacy of HD with depression; both were overlooked in several previous studies that resulted in an overestimation of the prevalence of depression in dialysis patients (14,15). We are planning a new survey that involves more patients from several dialysis centers with evaluation of pre and post-HD PHQ-9 scores to clarify the role of uremic symptoms on the diagnosis of depression, with longer follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the similarity of many depression symptoms such as lack of interest, poor appetite, insomnia, and weakness with symptoms of uremia, we instructed the patients to complete the PHQ-9 form the same day few hours' post-HD sessions, when uremic symptoms are the least. This critical precaution was overlooked in similar studies conducted formerly in the Middle and the Far East, that resulted in a considerable overestimation of the rate of depression in such patients (14,15). We categorized the patients, according to the results of the PHQ-9 scores, considering a score of 10 or more as an indicator of significant clinical depression that required intervention, on the other hand, scores more than 20 suggested severe depression that required psychiatric consultation or referral.…”
Section: Methodsmentioning
confidence: 99%
“…This situation negatively influences the quality of life of the subject and his/her caregivers, as well as decreases adherence to treatment and increases the rate of clinical complications and mortality [11–13]. …”
Section: Introductionmentioning
confidence: 99%